2013
DOI: 10.1038/nn.3329
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dynamics of CA1 hippocampal place codes

Abstract: Via Ca 2+ -imaging in freely behaving mice that repeatedly explored a familiar environment, we tracked thousands of CA1 pyramidal cells' place fields over weeks. Place coding was dynamic, for each day the ensemble representation of this environment involved a unique subset of cells. Yet, cells within the ∼15-25% overlap between any two of these subsets retained the same place fields, which sufficed to preserve an accurate spatial representation across weeks.CA1 place cells are considered crucial for spatial me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

142
1,274
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,012 publications
(1,429 citation statements)
references
References 26 publications
142
1,274
13
Order By: Relevance
“…There are many differences between these experiments (species, procedure, intervals between tests, background labeling) that could account for this difference. However, a recent study by Ziv et al (2013) used optical imaging to examine place cell reactivation in mice and found that 25% of neurons in CA1 (with active place fields) were reactivated in the same environment 5 d later. This number decreased slightly over time to 5% when sessions were separated by 30 d. In this study, the authors used calcium imaging and a miniaturized head-mounted microscope to monitor neural activity as mice traversed a linear track.…”
Section: Alternative Tagging Methodsmentioning
confidence: 99%
“…There are many differences between these experiments (species, procedure, intervals between tests, background labeling) that could account for this difference. However, a recent study by Ziv et al (2013) used optical imaging to examine place cell reactivation in mice and found that 25% of neurons in CA1 (with active place fields) were reactivated in the same environment 5 d later. This number decreased slightly over time to 5% when sessions were separated by 30 d. In this study, the authors used calcium imaging and a miniaturized head-mounted microscope to monitor neural activity as mice traversed a linear track.…”
Section: Alternative Tagging Methodsmentioning
confidence: 99%
“…This approach offers a level of temporal resolution and action potential sensitivity that is intermediate between physiological recording and IEG expression, with the advantage that the neurons are precisely identified anatomically and can be stably imaged over long time periods. This approach was used to simultaneously record the activity of between 500 and 1000 CA1 hippocampal neurons over 45 days while the animals ran on a linear track in a constant spatial environment (Ziv et al 2013). As seen in previous electrophysiological studies, on any given day, the neurons showed clear spatial firing fields with 20% of neurons meeting the criteria for place cells.…”
Section: Patterned Activity During Retrievalmentioning
confidence: 99%
“…And indeed, both theoretical (4) and experimental results from motor cortex (5,6) demonstrate that a network composed of unstable units may nonetheless exhibit stable performance. Recent recordings from the mouse hippocampus showed that reliable location signaling is driven largely by neurons that gradually enter and leave the population of functionally active place cells over the course of several days (7). In that study, only 15% of longitudinally monitored neurons were found to retain the same place fields in two sessions that were separated by one month.…”
mentioning
confidence: 91%